Does Abatacept Induce Testicular Toxicity? - Sultan AL-MOGAIREN (Archives of Rheumatology, 2020)
Objectives: This study aims to demonstrate the effect of subcutaneous injections of abatacept on the histology of testes in mice. Materials and methods: The study included 20 male BALB/c mice (average weight, 25 g; aged 12-14 weeks). Ten mice received subcutaneous (SC) injections of abatacept [0.25 mg per 25 g body weight per 0.03 mL normal saline (NS)] at zero, two, four and eight weeks. As the control group, 10 mice received SC injections of NS (0.03 mL). At the post-injection 10th week, the mice were sacrificed, and histopathological studies were conducted. Results: The results showed that 3/10 mice died of the abatacept-treated group. Testicular histology for the abatacept-treated group showed that 7/7 displayed no histopathological changes. Conclusion: To our knowledge, this is the first control-blinded study of BALB/c mice suggesting that abatacept may not have testicular toxicity. Further fertility and testicular toxicology evaluations including semen analysis and gonadal hormones should be performed to clarify our findings.